DEVELOPMENT OF ANDROID BASED LEARNING MEDIA TO INCREASE THE UNDERSTANDING OF DIFERENTIAL LESSONFOR ACCELERATION OF INTEREST IN LEARNING - Pujangga, Jajang; Komaro, Mumu; Muhammad Noor, Ridwan Adam (Universitas Pendidikan Indonesia, 2020)
The learning process can improve student learning outcomes and school quality. Benchmarks used are learning achievement refers to educational achievement that includes cognitive, affective and psychomotor aspects. Learning media are tools that can make learning activities effective. In fact there are still many students who find grades below the minimum graduation keriteria standards. The purpose of the research is to develop an Android-based interactive media which is appropriate to improve learning outcomes. This media helps students overcome difficulties in understanding on: understanding, function, component naming, work methods and working principles, how to care and stages of breathing and installing on Differential material. The research design uses the five stages of the ADDIE model of the research procedure using the One group Pretest-Posttest design. The result is the average student value of 12.80 in Pretest, after treatment the average value of Posttest increased to 83.23 with the highest value of96. This media is able to increase learning outcomes (N-gain), the results of this study showed thelearning media can increase student interest in learning.